The Relationship between Physical Work Environment, Non-Physical Work Environment, and Organizational Commitment on the Performance of Nurses in the Inpatient Ward of Kendari City Hospital - Nuraena, Siti; Yuniar, Nani; Prasetya, Fikki (PT. Riset Press International, 2024)
Nurse performance is the effort of nurses in carrying out their duties and responsibilities to the best of their abilities, in order to achieve the main goals of the profession and organizational objectives. The purpose of this study is to examine the physical work environment's impact on the performance of nurses in the Inpatient Ward of Kendari City Hospital, the non-physical work environment's impact on the performance of nurses in the Inpatient Ward of Kendari City Hospital, and organizational commitment's impact on the performance of nurses in the Inpatient Ward of Kendari City Hospital. Data analysis was conducted using SPSS statistical tests including univariate, bivariate, and multivariate analyses. The sample size for this study was 95 individuals, and the sampling technique used was the census method. The results of this study indicate that the physical work environment significantly influences the performance of nurses in the Inpatient Ward of Kendari City Hospital with a p-value of 0.028 < 0.05. The non-physical work environment also significantly influences the performance of nurses in the Inpatient Ward of Kendari City Hospital with a p-value of 0.009 < 0.05. Organizational commitment significantly influences the performance of nurses in the Inpatient Ward of Kendari City Hospital with a p-value of 0.017 < 0.05. Recommendations from this study include the need for management to improve the physical work environment, particularly in terms of ventilation and cleanliness, to enable nurses to perform well